Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Bank Bengkulu Cabang Mukomuko - Zusmawati, Zusmawati; Zolmi, Zolmi (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
The purpose of this study was to examine the effect of the variables of Work Discipline and Work Environment on Employee Performance at PT. Bank Bengkulu Mukomuko Branch. Data collection by distributing questionnaires to 31 respondents using saturated sampling technique, where all members of the population are sampled, using data processing techniques validity test, reliability test, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression testing and test t with the help of the SPSS application. The results of the study show that work discipline has a positive and significant effect on the performance of employees of PT. Bank Bengkulu, Mukumuko branch, and the work environment have a positive and significant effect on the performance of employees of PT. Bank Bengkulu Mukomuko Branch.